PENGARUH JENIS LOGAM KONTAK AL, AG DAN CU PADA KARAKTERISTIK DIODA SEMIKONDUKTOR ISOLATOR LOGAM (SIL) - -, Uminingsih (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2005)
The metal insulator semiconductor with metal contacts of of Ag, Al,Cu and insu-lator of toluene has been fabricated, characterized and investigated. The experimental results show that the current voltage (I-V) characteristic of MIS (Metal Isolator Semicon-ductor) diode is effected by type of metal contact. The cut in and breakdown voltages for the n-type silicon semiconductor are 1,1 -1.3 volt and 200 – 240 volt where for the p –type silicon semiconductor the cut in and breakdown voltages are 0,8 -1.0 volt and 120 – 180 volt. Also the experimental data show that I –V characteristics of MIS diode have bigger Cu in and breakdown voltages compare with those of junction and Schottky dio-des. From the investigation it can be summarized that metal contact with higher work function is suitable for p–type silicon semiconductor (Ag/T/Si-p/Al) where metal contact with higher work function is suitable for n-type silicon semiconductor (Ag/T/si-n/Al). The-se types of metal contacts provide higher cut in and breakdown voltages.